Impact of Sand Mining on Bathymetry of the Meghna River (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
This study aims to evaluate the morphological changes of the lower Meghna River in Bhola district due to reckless sand mining from riverbeds. It has been done based on primary data collected from the field and secondary data, such as river bathymetry of 2006, 2012, and 2022 from BIWTA and Landsat Imageries of 2006, 2016, and 2023 from USGS Earth Explorer. The study demonstrates that extensive sand mining activities in the lower Meghna River significantly affect river bathymetry and accelerate riverbank erosion. Lower Meghna River experiences a higher erosion rate due to prolonged and intensive sand mining. The erosion rate increased significantly between 2020 and 2021, with the riverbed eroding at an accelerating rate, highlighting a critical situation in the region. However, FGD and case studies from the field show that the impact of sand mining is not only confined to river morphology change but many more ecological, socio-political, economic, environmental, and governance issues are also linked with sand mining activities.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 13(1), 2024, P 21-28